2013
DOI: 10.1016/j.biortech.2013.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Parametric sensitivity analysis for temperature control in outdoor photobioreactors

Abstract: In this study a critical analysis of input parameters on a model to describe the broth temperature in flat plate photobioreactors throughout the day is carried out in order to assess the effect of these parameters on the model. Using the design of experiment approach, variation of selected parameters was introduced and the influence of each parameter on the broth temperature was evaluated by a parametric sensitivity analysis. The results show that the major influence on the broth temperature is that from the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…In countries with high irradiance, the water temperature in some outdoor cultivation systems may increase due to the solar intensity. For example, the temperature in a photobioreactor can be above 35°C (Pereira et al 2013). This high temperature adversely affects the growth of microalgae not adapted to these conditions, e.g., Bamba et al (2015), and can be lethal for a number of species (Barsanti and Gualtieri 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In countries with high irradiance, the water temperature in some outdoor cultivation systems may increase due to the solar intensity. For example, the temperature in a photobioreactor can be above 35°C (Pereira et al 2013). This high temperature adversely affects the growth of microalgae not adapted to these conditions, e.g., Bamba et al (2015), and can be lethal for a number of species (Barsanti and Gualtieri 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several studies reported on the development of temperature models and complementary research involving various types of microalgae cultivation systems. Those studies differ widely in terms of scope (e.g., type of reactor system) and levels of accuracy. One of the most advanced temperature models for a closed photobioreactor system has been reported by Béchet et al , Their model computes the reactor’s heat balance as a function of various static and dynamic parameters for a bubble column reactor concept, a system mostly used in laboratory-scale experiments.…”
Section: Introductionmentioning
confidence: 99%
“…The reported approach thus neglects shading effects that naturally occur in larger applications. To date, shading effects on reactor temperature have only been taken into account by a single study . However, in the respective publication shading was only examined as a static parameter, neglecting the effects of the sun’s position with respect to the orientation and geometry of the panels.…”
Section: Introductionmentioning
confidence: 99%
“…Providing accurate parameters is indeed crucial since model-based optimality might be sensitive to parameters values as shown in [3]. Moreover, assessing the effect of operational factors via sensitivity analysis can provide useful information for improving configuration design of photobioreactors [4].…”
Section: Introductionmentioning
confidence: 99%